2021
DOI: 10.11648/j.ijeedu.20211001.14
|View full text |Cite
|
Sign up to set email alerts
|

Social Support Programs and Teachers’ Performance in Private Primary Schools in Bomet County, Kenya

Abstract: Despite the use of social support programs, teacher's performance in private primary schools is still very low. The research sought to evaluate influence of social support programs on teacher's performance of different private-owned primary schools within Bomet County. In addition, the study was anchored functional theory of labor welfare. Moreover, descriptive research design was used in this research. The target population was 132 privately-owned primary schools in Bomet County. Stratified random sampling te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The study found that the psychological contract's strength determines an organization's capacity to get the best out of its personnel. In another similar study, of social support programs and performance of academic staff of primary schools in Bomet county by Omariba and Bula [27], findings indicate that social support programs have a positive and a significant effect on teacher's performance of academic staff Additionally, survey showed financial assistance, emotions support and guidance and counseling affect teacher's performance in private primary schools within Bomet County. This is evident that relational support has a big bearing on the performance of academic staff at any level.…”
Section: Empirical Literature Reviewmentioning
confidence: 86%
“…The study found that the psychological contract's strength determines an organization's capacity to get the best out of its personnel. In another similar study, of social support programs and performance of academic staff of primary schools in Bomet county by Omariba and Bula [27], findings indicate that social support programs have a positive and a significant effect on teacher's performance of academic staff Additionally, survey showed financial assistance, emotions support and guidance and counseling affect teacher's performance in private primary schools within Bomet County. This is evident that relational support has a big bearing on the performance of academic staff at any level.…”
Section: Empirical Literature Reviewmentioning
confidence: 86%
“…Reporting and performing service in natural situations.". According to Patton, that "Qualitative method is to understand phenomena that are occurring naturally (naturally) in circumstances that are occurring naturally" (Omariba Ogari & Hannah Orwa, 2021). This is suitable for this service which is intended to describe the reality of implementing village apparatus empowerment through a non-formal education approach in the context of alleviating poverty in the village.…”
Section: Introductionmentioning
confidence: 99%